1999
DOI: 10.1074/jbc.274.26.18741
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Plasma Membrane H+-Biotin Symporter of Saccharomyces cerevisiae by Rescue of a Fatty Acid-auxotrophic Mutant

Abstract: Bakers' yeast is auxotrophic for biotin (vitamin H) and depends on the efficient uptake of this compound from the environment. A mutant strain with strongly reduced biotin uptake and with reduced levels of protein biotinylation was identified. The strain was auxotrophic for long-chain fatty acids, and this auxotrophy could be suppressed with high levels of biotin in the medium. After transformation of this mutant with a yeast genomic library, the unassigned open reading frame YGR065C was identified to compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 45 publications
4
76
1
Order By: Relevance
“…We demonstrated before that protonophores cause a severe reduction in the activity of known proton-vitamin symporters (22,40,43). We repeated some of these experiments and found that biotin uptake, for example, is reduced to 25% of controls by the addition of 0.1 mM carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (data not shown).…”
Section: The Function Of Mch5 Is Unique Within the Mch Gene Familymchmentioning
confidence: 78%
“…We demonstrated before that protonophores cause a severe reduction in the activity of known proton-vitamin symporters (22,40,43). We repeated some of these experiments and found that biotin uptake, for example, is reduced to 25% of controls by the addition of 0.1 mM carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (data not shown).…”
Section: The Function Of Mch5 Is Unique Within the Mch Gene Familymchmentioning
confidence: 78%
“…Biotin is taken up by VHT1, a plasma membrane biotin transporter (Stolz et al 1999). Many prokaryotes are capable of synthesizing biotin, as are plants and some fungi.…”
Section: B Iotin (Vitamin H) Is An Essential Vitamin Inmentioning
confidence: 99%
“…Mutation of the glycosylation sites at N138 and N489 reduced the V max of the importer activity, but did not affect the affinity for biotin, implying a key role of the sugar moieties in the activity of the transporter [68]. Likewise, posttranslational phosphorylation of SMVT is utilized to regulate SMVT activity [69]. This was demonstrated in colorectal adenocarcinoma cells where the addition of protein kinase C activators reduced uptake of biotin whereas the presence of kinase inhibitors stimulated its uptake [60].…”
Section: Mammalian Sodium -Dependent Multivitamin Transporter (Smvt1)mentioning
confidence: 69%
“…MCT1 has also been proposed as an alternative mammalian biotin transporter in cells of the lymphoid lineage [71], despite these cells also expressing a functional SMVT [69]. In mammalian colonic luminal membrane vesicles, MCT1 acts as the main protein that facilitates translocation of bicarbonate ions from the colonic lumen into colonocytes [72].…”
Section: Mammalian Monocarboxylate Transporter (Mct)mentioning
confidence: 99%